Peripheral T‐cell and NK‐cell lymphomas and their mimics; taking a step forward – report on the lymphoma workshop of the XVIth meeting of the European Association for Haematopathology and the Society for Hematopathology. Issue 2 (16th October 2013) - Attygalle, Ayoma D; Cabeçadas, José; Gaulard, Philippe; Jaffe, Elaine S; de, Daphne; Ko, Young Hyeh; Said, Jonathan; Klapper, Wolfram
<x xml:space="preserve">Abstract</x> Mature T‐cell and T/NK‐cell neoplasms are both uncommon and heterogeneous, among the broad category of non‐Hodgkin lymphomas. Owing to the lack of specific genetic alterations in the vast majority, most currently defined entities show overlapping morphological and immunophenotypic features, and therefore pose a challenge to the diagnostic pathologist. In the light of recent immunophenotypic, cytogenetic and molecular genetics advances in the field of T‐cell and T/NK‐cell lymphomas, the focus of the lymphoma workshop of the European Association for Haematopathology/Society for Hematopathology meeting in Lisbon, Portugal, in October 2012 was to refine existing diagnostic criteria and clarify the borders between overlapping entities. The panel reviewed over 200 submitted cases, which were grouped into five categories: (i) angioimmunoblastic T‐cell lymphoma and T‐follicular‐helper‐cell‐associated lymphomas; (ii) CD30‐positive T‐cell lymphomas/lymphoproliferative diseases; (iii) extranodal T‐cell and NK‐cell neoplasms; (iv) EBV‐associated T‐cell/NK‐cell lymphomas/lymphoproliferative diseases; and (v) peripheral T‐cell lymphoma, not otherwise specified, post‐transplant lymphoproliferative disorders, and mimics. This report summarizes the discussions and conclusions of the workshop, which question current diagnostic criteria and provide recommendations for refining existing classifications.